Primary penile melanoma (2016)
Primary penile melanoma is a rare entity, characterized by rapid metastases and associated with poor prognosis. Its diagnosis and treatment is usually late, with serious consequences and a high mortality rate. The purpose of this review is to describe our experience in the diagnosis, management and presentation of a new clinical case of primary penile melanoma. © 2015 Sociedad Colombiana de Urología.